At the Heart of Texas : One Hundred Years of the Texas State Historical Association, 1897-1997 - McCaslin, Richard B. (Book collections on Project MUSE., 2014)
Founded in 1897, when the state of Texas was just half a century old, the Texas State Historical Association soon became known as the nation's most dynamic regional history organization. Earlier attempts to organize historical societies in Texas, traced in the opening chapter, illuminate the factors that came ultimately to be decisive in the success of the Association: the wisdom in linking the organization with the University of Texas, the inclusion of lay historians, and the continued insistence on high academic standards. Within the larger framework of the directors, the programs, and.